Estudio de incumplimiento de las declaraciones del impuesto al valor agregado y su incidencia en el nivel de multas aplicadas a la microempresa familiar Cyber Café Los Cañones - Mosquera Medrano, Carlo Julio (2021)
Failure to comply with tax returns affects public income in its entirety, since it produces insufficient resources required to meet collective needs, causing a detrimental effect on society, it is for this reason that failure to comply with tax returns Added tax offices have been installed in various sectors of the Province, in order to control and improve tax collection, reducing the leakage, but this objective is not fully met; Many of the taxpayers do not have the necessary knowledge about the tax obligations that they must comply with, causing them sanctions. Within tax revenues, the tax that contributes the most to the General State Budget is VAT; the same that is a tax that Ecuadorians pay when certain goods and services are acquired. The purpose of this case study is to determine how non-compliance with Value Added Tax returns affects the level of fines. The methodology to be used is descriptive, explanatory, field and quantitative, since we will use the interview as a means of investigation. A detailed study will be carried out on the non-compliance of the added value and its incidence on the fines applied that have the family micro-business Cyber Café Los Cañones, in order to reduce tax non-compliance, increase the tax culture and submit VAT returns in the established time, the same that is carried out according to the ninth digit of the RUC, and that the declaration is made correctly.